2021
DOI: 10.1007/s00402-021-04060-2
|View full text |Cite
|
Sign up to set email alerts
|

No increased injury incidence in the German Bundesliga after the SARS-CoV-2 virus lockdown

Abstract: Introduction The coronavirus lockdown in 2020 resulted in a worldwide suspension of professional sports. The first major professional football league to restart after the lockdown was the German Bundesliga. This study investigates whether the injury incidence increased after the restart of the season with only 9 days of regular preparation time and without any friendly matches in comparison to three control periods. Materials and methods In a prospective c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 27 publications
1
18
2
2
Order By: Relevance
“…This increase in the rating of match injury was mostly associated with muscle-type injuries, particularly because of an abnormal number of injuries at the first matchday after the resumption of the championship. However, in the study by Krutsch et al [ 14 ], injury incidence in the matches played after the lockdown were similar to the pre-lockdown period. Interestingly, these two investigations present some contradictory results despite analyzing the same event.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…This increase in the rating of match injury was mostly associated with muscle-type injuries, particularly because of an abnormal number of injuries at the first matchday after the resumption of the championship. However, in the study by Krutsch et al [ 14 ], injury incidence in the matches played after the lockdown were similar to the pre-lockdown period. Interestingly, these two investigations present some contradictory results despite analyzing the same event.…”
Section: Discussionmentioning
confidence: 88%
“…The only published information describing the effect of lockdown due to the COVID-19 pandemic on injury epidemiology has been provided with data from the Bundesliga [ 13 , 14 ]. Seshadari et al [ 13 ] found a significant increase in the number of injuries per match in the Bundesliga after the resumption of the competition, at least in comparison to pre-lockdown.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations